(untitled) (The Pakistan Development Review, 2000)
Monetary economics provides one of the important tools, that is monetary policy, to deal with the macroeconomic problems of the economy. It is concerned with the supply of money and the demand for money. It is often assumed that the money supply is exogenously determined by the authorities and the demand for real money is determined by the market. The demand for money is of crucial importance in the conduct of monetary policy. It helps to understand macroeconomic activities and to prescribe appropriate policy instruments to deal with macroeconomic problems. The effectiveness of the monetary policy, however, depends on the shape and stability of the estimated demand for money function.